The EVALUATION OF THE USE OF ANTI-INFLAMMATORY DRUGSIN PATIENTS RHEUMATOID ARTHRITIS OUTPATIENT AT GRANDMED HOSPITAL LUBUK PAKAM - Sihombing, Yanna Rotua; Marbun, Romauli Anna Teresia; Zebua, Kristian Cahayani; Lestari, Dayana (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Rheumatoid arthritis is an autoimmune disease characterized by inflammation of the joints that can become chronic. Rational use of drugs aims to ensure that patients get safe and effective treatment in the right time frame and at an affordable price according to their needs In the outpatient facility of Lubuk Pakam Hospital, patients experience symptoms such as pain, inflammation, morning joint stiffness and difficulty moving at appropriate doses. This study aims to aim to obtain an objective picture or picture of the situation. Data collection was carried out retrospectively, namely by observing the medical records of rheumatoid arthritis patients at Grandmed Lubuk Pakam Hospital in 2021. A total of 13 (56.5%) female patients and 10 (56.5%) (43.5%) male patients, according to the number of rheumatoid arthritis patients at the outpatient facility of GrandMed Lubuk Pakam Hospital in 2021. This makes the inclusion criteria for all anti-inflammatory agents incomplete in rheumatoid arthritis and the exclusion criteria for all medical records in rheumatoid arthritis patients. Analysis of data based on age, gender, rationality of the drug, correct indications, correct patient, correct drug, correct dosage. The Outpatient Study of GrandMed Lubuk Pakam Hospital 2021 is: Correct Indications (100%), Correct Patients (100%), Correct Drugs (100%), Correct Dosage (91.3%). The treatment of patients with rheumatoid arthritis at GrandMed Lubuk Pakam Hospital can still be said to be fully good